Automatic Punctuation Verification of School Students’ Essay in Portuguese - de Lima, Tiago Barbosa; Rodrigues, Luiz; Macario, Valmir; Freitas, Elyda; Mello, Rafael Ferreira (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2023)
Textual production is a key activity at different levels of education. The analysis of essays encompasses several criteria, such as lexical and syntactic errors, cohesion, and coherence. Within these criteria, how the students include punctuation (i.e., final mark and comma) could influence the quality of the final production. Thus, the literature has proposed several approaches to verifying punctuation correction in students’ essays for English. However, despite the advancements in natural language processing models for other languages, there is a significant gap concerning punctuation verification. Therefore, this paper proposed a new approach based on state-of-the-art language models to develop a punctuation prediction method for Portuguese. The proposed model was applied to evaluate the textual productions of students in Brazilian public schools. Finally, the results of this study and its practical implications for educational settings are further discussed.